EFEKTIVITAS ANALISIS SWOT DALAM MENINGKATKAN MUTU PEMBELAJARAN DI SDI MIFTAHUL DINIYAH - Nurafifah Luthfiyani; Hinggil Permana (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2022)
In educational institutions (schools) the quality of learning affects the success of schools in the context of the dynamics of changing times that are increasingly advanced. The development of an educational institution is seen from its students who are required to participate in shaping and improving the quality of learning so that educational output can compete in the realm of change well. What will be done is to improve the quality or quality of school learning effectively through a SWOT analysis, namely strength (strength), weakness (weakness), opportunity (opportunity) and threat (threat). Each of these analyzes will show factors or variables that will determine how appropriate the level of learning quality at SDI Miftahul Diniyah in South Tangerang is in order to determine the effect of improving the quality of learning which will produce ideas of success in accordance with existing learning quality standards.Keywords: SWOT Analysis, Quality of Learning